Eksplorasi Properti Psikometrik Kuesioner Takwa kepada Allah Ta'ala - Irwan Nuryana Kurniawan (JURNAL PSIKOLOGI, 2018)
Although Takwa kepada Allah Subahanahu wa Ta’ala became one of the main indicators for the success of national education goals, so far the learning evaluation at all educational level in Indonesia only provides information on academic achievement alone. The present study is expected to provide a valid and reliable learning evaluation instrument related to non-academic important indicators of national education objectives. The current study is a further study aimed at exploring psychometric properties Takwa toward Allah Subahanahu wa Ta’ala Questionnaire (KTA; Fikri & Kurniawan, 2013). The study involved 220 Islamic boarding school students, comprised 57.3% male students and 42.7% female students, and their age ranges 15 years old to 27 years old (M=17.7, SD=1.90). For the purposes of validating the KTA, Surrender to God Scale (SGS; Wong-McDonald & Gorsuch, 2000), Flourishing Scale (FS; Diener, Wirtz, Tov, Kim-Prieto, Choi, Oishi, & Biswas-Diener, 2009), Negative Affect Subscale of SPANE (NA Subscale of SPANE; Diener, Wirtz, Tov, Kim-Prieto, Choi, Oishi, & Biswas-Diener, 2009), and Reynolds Short-Form of Marlowe-Crowne Social Desirability Scale (RSF-MCSDS; Reynolds & Gerbasi, 1982) were administered to them. The results of the study demonstrated the KTA has satisfying early psychometric evidence as a learning evaluation instrument. The findings, implications, and limits of the study are briefly discussed.